PELATIHAN KETERAMPILAN MENGAJAR BAGI GURU MADRASAH IBTIDAIYYAH DI AMBULU JEMBER - Muhammad Ibnu Faruk Fauzi (PENA DIMAS: Jurnal Pengabdian Masyarakat, 2022)
This Community Service aims to organize a Teaching Basic Skills Refreshment Training for teachers of ibtidaiyyah Madrasah in Ambulu Jember, besides that the training participants are able to master the concept of basic teaching skills of teachers as a prerequisite for the implementation of the independent learning program in the classroom, and participants are able to change the views and attitudes of teachers who have a feudal character to the character of humanism teachers. The method used in this community service is to use the lecture method, question and answer and practice or direct simulation. The results of this programs findings obtained are that teachers in carrying out learning must have the ability of teaching skills which include first the skills of opening and closing lessons. Secondly, the skill of explaining the lesson. Third, the skill of asking. Fourth, skills give reinforcement. Fifth, the skill of holding variations. Sixth, the skill of guiding small group discussions. Seventh, individual/individual teaching skills. Eighth, the skill of managing classes.